Slingin' Sam : the Life and Times of the Greatest Quarterback Ever to Play the Game - Holley, Joe (University of Texas Press, 2012)
"Dan Jenkins calls Baugh "the greatest quarterback who ever lived, college or pro." Even though he played for the Washington Redskins mostly in the pre-TV era (1937-1952), he is still remembered and revered by fans, who consistently name him as the former player they would most like to see back in the game. Baugh was one of the first inductees into the Pro Football Hall of Fame. A living link between the leather-helmet era and the modern, Baugh spread the field, opened up the game, and made the forward pass a strategic weapon, not a desperation heave. He made quarterback the glamour position, which means that Peyton Manning, Tony Romo, Tom Brady, and all the other football field generals since Baugh are in his debt"--